Trends in Brazilian productions on the assistive technologies’ effectiveness for patient safety - Christiani Andrea Marquesini Rambo; Giulia Dos Santos Goulart; Eveline do Amaral Antonello; Tânia Solange Bosi de Souza Magnago; Yuliett Mora Pérez; Graziella María Rosa Cauduro (Medisur)
Patient safety in healthcare institutions is essential for quality healthcare. This work constitutes a narrative review of the literature for identifying trends, in Brazilian theses and dissertations, on the evaluation of the assistive technologies’ effectiveness to promote patient safety. Data collection was in June 2023, from the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel database. Two search strategies were used, associating the keywords. Studies that answered the guiding question were included. Data analysis was carried out through exploratory, analytical and interpretive reading of the studies. Descriptive data were analyzed using descriptive statistics. The corpus was made up of 13 studies. Of which nine (69.2%) were dissertations, developed between 2009 and 2022, produced in public education institutions (92.3%), in postgraduate nursing programs (30.8%), in the state of São Paulo (30.8%). The predominant methodological design was the quasi-experimental study (46.1%) and the most used technology was the protocols (38.5%), related to the international objective of preventing health-related infections (30.8%). Most of the technologies used were found to be effective. Among them, protocols stood out as important tools to guide clinical practice; however, there is a need to wide research and explore different assistive technologies to obtain a more comprehensive understanding of interventions capable of improving patient safety.